Handling peer pressure - Cambridge Educational (London : Cambridge Educational, 2011)
The teen years are a time of experimenting with identity, but along with that search for self come major decisions about what groups to fit into--and how to fit into them. This video explores peer group influences; how they can cause young people to change their attitudes, values, or behaviors in order to conform; and what can be done to avoid their pitfalls. Topics include positive, negative, direct, and indirect peer pressure; cultural forces, especially media-driven ones, that push the desire to be a'star' instead of making a genuine journey of self-discovery; and media stereotypes of what it means to be attractive, smart, or successful. The program also looks at how friendship groups can become cliques, how low self-esteem leads some people to manipulate or intimidate others to fit in, and how peer pressure, as pervasive as it is, can be countered with honesty, self-expression, and self-knowledge.
DVD format
Keywords: Peer pressure; Conformity